PELAKSANAAN DAN PENGATURAN PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT DI DESA ARGOPENI KECAMATAN AYAH KABUPATEN KEBUMEN - , M.WAHYU SATRIA, Ibu Dr. Jur. M.Jur. Any Andjarwati, S.H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Community forest management is a system of forest management conducted jointly by the Perum Perhutani forest village communities , or Perum Perhutani and forest villagers with interested parties ( stakeholders ) , based on an agreement so that the interests together to achieve sustainability of the functions and benefits of forest resources optimal and proportional This study aims to look at setting up joint forest management program in the community Argopeni village , subdistrict father , Kebumen particularly with regard to the sharing agreement under Law No. 2 of 1960 . There are 3 formulation of the problem discussed in the writing of this law are: a ) How will the Forest Management Agreement in Argopeni village, subdistrict Ayah, Kebumen associated with production sharing agreements by Act No. 2 of 1960 ?